1998
DOI: 10.1530/eje.0.1380707
|View full text |Cite
|
Sign up to set email alerts
|

Identification and initial characterization of stathmin by the differential display method in nerve growth factor-treated PC12 cells

Abstract: The differential display of mRNA is a new strategy to identify genes that are differentially expressed under altered conditions. We applied this method to determine differential gene expression in the rat pheochromocytoma cell line during differentiation induced by nerve growth factor (NGF).Three different mRNA species were isolated, and their differential expression was confirmed by RT-PCR. One of the mRNA species was identified as stathmin, a 19 kDa cytosolic protein attracting increasing interest for its ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…Stathmin expression was described previously in PC12 pheochromocytoma cells where its expression was increased after nerve growth factor treatment which stimulated phosphorylation of stathmin [11,12]. A stathmin-like gene, which belongs to the stathmin family of phosphoproteins, RB3, was also reported in the rat hypothalamus [13].…”
Section: Introductionmentioning
confidence: 80%
“…Stathmin expression was described previously in PC12 pheochromocytoma cells where its expression was increased after nerve growth factor treatment which stimulated phosphorylation of stathmin [11,12]. A stathmin-like gene, which belongs to the stathmin family of phosphoproteins, RB3, was also reported in the rat hypothalamus [13].…”
Section: Introductionmentioning
confidence: 80%
“…Stathmin expression in decidualization (Puissant et al 1995), pheochromocytoma cells (Takekoshi et al 1998), and the gonadotrope (Drouva et al 1995); it might be associated with glandular proliferation or morphological changes. Interestingly, we found in our present study that the stathmin signals in human endometrial tissue were distinctly localized to the stromal cells of the functional area rather than the endometrium close to the myometrium (the stratum basale).…”
Section: Poly(a)mentioning
confidence: 99%
“…Total RNA was extracted as described previously (Takekoshi et al, 1998). Semi-quantitative PCR was performed according to a described method (Wizigmann-Voos et al, 1995;Meister et al, 1999).…”
Section: Isolation Of Mrna and Semi-quantitative Rt-pcr Analysismentioning
confidence: 99%
“…The reaction was carried out in a Program Temp Control System, Gene Amp PCR System 9600 (Perkin-Elmer-Cetus, CA). A program of 30 cycles was chosen on the basis of previous results and preliminary experiments (Wizigmann-Voos et al, 1995;Takekoshi et al, 1998) that demonstrated a linear relationship between the input DNA and the RT-PCR product obtained under these conditions. Human GAPDH sense (5V-CGA TGC TGG CGC TGA GTA C) and antisense (5V-CGT TCA GCT CAG GGA TGA CC) oligonucleotides were used as an internal standard.…”
Section: Isolation Of Mrna and Semi-quantitative Rt-pcr Analysismentioning
confidence: 99%